Analysis of The Use of Management Accounting Information In Determining The Business Strategy of UMKM D’KulinerBnB - Billa Eka Putri, Shalsa; Hwihanus, Hwihanus (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study investigates how the business strategy of D'KulinerBnB MSMEs uses management accounting information. With a qualitative approach through interviews, it was found that this MSME has implemented a management accounting system for financial recording, cost analysis, and business strategy. The use of accounting data helps with cost efficiency and fact-based decision-making. However, challenges such as limited knowledge, access to technology and human resources are still faced. To overcome them, business owners plan to improve accounting literacy, adopt digital technology and build networks with other MSMEs. In conclusion, management accounting plays an important role in a more effective and sustainable business strategy.